Autocrine and paracrine IL-6 is necessary to induce phagocytosis of viable neurons by brucella abortus-activated microglia - Rodríguez, Julia (2022)
Central nervous system infection by bacteria of the genus Brucella results in an inflammatory disorder called neurobrucellosis. We have previously demonstrated that soluble mediators released by B. abortus-infected astrocytes induce inflammatory activation of microglia and phagocytosis of viable neurons. We have also demonstrated that neutralization of IL-6 in neurons/microglia co-cultures treated with supernatants from B. abortus-infected astrocytes inhibits neuronal death, and this effect is caused by a decrease in the phagocytic activity of microglia. Considering that both astrocytes and microglia are capable of secrete IL-6, we aimed to investigate the contribution of each cell type in this phenomenon. Astrocytes from wild type (WT) and IL-6 KO mice were infected or not with B. abortus for 24 h. After that, cell-free culture supernatants were used to stimulate primary murine co-cultures of WT and IL-6 KO microglia with neurons during 48 h. Neuronal density was evaluated by fluorescence microscopy. Treatment of WT co-cultures with supernatants from IL-6 KO infected astrocytes caused a partial inhibition of neuronal death (p<0.05). Similar results were obtained when neurons/IL-6 KO microglia co-cultures were treated with supernatants from WT- infected astrocytes (p<0.05). Furthermore, neuronal loss was totally prevented in co-cultures of neurons/IL-6 KO microglia treated with IL-6 KO infected astrocytes (p<0.005). Moreover, B. abortus-activated microglia from IL-6 KO mice were unable to induce neuronal death (p<0.05).To evaluate the role of IL-6 in neuronal loss induced by microglia directly activated by B. abortus, we stimulate co-cultures of WT and IL-6 KO microglia with heat-killed B. abortus (HKBA). Activated IL-6 KO microglia were unable to induce neuronal death (p<0.05). These results indicate that both paracrine and autocrine IL-6 signaling in microglia can be sufficient to induce phagocytosis of viable neurons in the context of a B. abortus infection, and could highlight the relevance of this cytokine in neuropathological mechanisms caused by Brucella spp.